Analysis of the Quality of Assurance Statements on Corporate Sustainability Reports on the Stock Exchanges of Several Countries in the World in 2020-2022 - Nangoy, Gavriel Faith; Meiden, Carmel (AIBPM Publisher, 2023)
While sustainability reporting has experienced notable advancements in recent years, a discernible gap persists between the progress in reporting practices and the corresponding assurance measures. This paper emphasizes the degree to which the contents of sustainability assurance statements align with the essential elements mandated by the ISAE 3000 and AA1000AS assurance standards. A content analysis was performed for the assurance statements of twenty-four (24) public listed companies listed on 24 different exchanges over a three-year span from 2020 to 2022. This analysis employed a quantitative approach involving scoring to assess the alignment of the content with the requirements of the assurance standards. The research instrument used were based on the minimal content elements of ISAE 3000 and AA1000 AS and developed by previous studies. The results of this study describe variability in the quality of assurance statements based on assurance standards, assurance provider, country of origin, industry sector, and content element. This research contributes to the existing literature in sustainability assurance through content analysis offering a nuanced global perspective through a large sample size and utilizing a streamlined research instrument derived from previous studies, enhancing the precision and conciseness of the analysis.